Is increasing inequality harmful? Experimental evidence - Dietmar Fehr (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
Increasing inequality is commonly associated with social unrest and conflict between social classes. This paper reports the results of a laboratory experiment to study the implications of rising inequality on the tendency to burn others' income. The experiment considers an environment where higher earnings are typically associated with higher effort and varies how fair and transparent this relationship is. The findings indicate that increasing inequality does not per se lead to more money burning. Rather, it depends on whether the increase in inequality can be unequivocally attributed to exerted effort. If subjects can tweak the income-generating process in their favor, money burning is substantially higher. Low-income subjects are more likely to burn others' income and most of the money burning is aimed at subjects with higher incomes.
Keywords: C72; C92; 330; inequality; money burning; fairness